EVALUASI EFEKTIVITAS TERAPI RINITIS ALERGI DI INSTALASI RAWAT JALAN RS PANTI RAPIH YOGYAKARTA - , BERNADINE AMANDA N; , Prof. Dr. Zullies Ikawati, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Allergic rhinitis is a symptomatic nasal disease caused by inhaled allergen exposure which is characterized by inflammation of the nasal mucous membrane mediated by immunoglobulin E (IgE). Symptoms of allergic rhinitis are sneezing, nasal congestion, rhinorhea, and red, watery eyes. This study was done to figure out the effectivity of allergic rhinitis therapy in Instalasi Rawat Jalan RS Panti Rapih Yogyakarta. This study was non-experimental and were done with descriptive data analysis. Data were collected prospectively, using purposive sampling technique. Symptoms suffered by patients were asssesed based on Total Nasal Symptom Score (TNSS) including sneezing, nasal congestion, watery nose, and itchy nose symptom score. The data were collected from a questionnaire which is filled by patients twice, the first time was when patients were just diagnosed from allergic rhinitis for new patients, or when patient did the medical check-up in the hopital for old patients, and the second time was two weeks after the first data collection. 31 patients participated in this study. The result showed that the drug class used were antihistamines, decongestants, and corticosteroids. Drug that was most commonly used were antihistamines. The result also revealed that after two weeks of therapy most patientsâ symptoms got better. There is tendency of influence between the number of drug combination given to patients and patientsâ symptoms severity to the effectivity of allergic rhinitis medication. However, this study still couldnât conclude about the most effective drug combination, due to limited period of study and number of subject.